A Festschrift for a Consciousness Hummingbird: Charles T. Tart - Cardeña, Etzel (Journal of Anomalous Experience and Cognition, 2023)
Charles Tart was arguably the most important theoretician and researcher of altered states of consciousness (ASC) during the second half of the 20th century. His vast output included books and articles extending the frontiers of study of states of consciousness in general, and of the hypnagogic state, dreaming, meditation, hypnosis, and minor and major psychedelic drugs, among others. Rather than a specialized scientist, he was a fast and agile hummingbird who did not visit only a flower or two but extracted noetic nectar from many more and proceeded to pollinate a wide field of study that had mostly lain barren since the early contributions by William James and a few others. In this editorial I provide a general introduction to his work and its influence on mine.